The Religious Moderation Discourse in Social Media: Studies on Ach Dhofir Zuhry’s Facebook and YouTube - Iswanto, Agus; Maknun, Moch Lukluil; Hidayat, Roch Aris; Nugroho, Muhammad Aji (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
There have been many studies discussing the use of social media for disseminating the religious ideology of both conservatism and radicalism. On the contrary, there have been a few studies that deal with how the moderate groups disseminate the discourse of religious moderation, whereas this topic is significant and needs to be discussed to view the strength and weaknesses as well as the contestation between each group. This article presents the production, distribution, consumption, and social practice of the religious moderation discourse throughout the content delivered by the figure from the groups of moderate Islam, from the Regency of Malang. The article is based on the discourse analysis of several pieces that have been produced by the figure and his team on YouTube and Facebook. The study shows that the production of religious moderation discourse in social media is carried out in two ways: conveying messages of religious moderation and countering narratives of conservatism and religious radicalism. The prospect of Islamic moderation discourse holds the opportunity to gain success in countering the narration of religious radicalism. However, the success of discourse contestation is defined by the strength of its distribution.